Importance of Nonhuman Primates as a Model System for Gene Therapy Development in Ophthalmology - Wozar, Fabian; Seitz, Immanuel; Reichel, Felix; Fischer, M. Dominik (Klinische Monatsblätter für Augenheilkunde, 2022)
Gene therapy is a treatment concept that uses, in most cases, viral vectors to deliver a therapeutic transgene to target cells. Although the idea of gene therapy dates back over 50 years ago, due to the complexity of the treatment concept, it took until the last decade for the responsible agencies like FDA and EMA to recommend the first gene therapy products for clinical use. The development of these therapies relies on molecular engineering of specifically designed vectors and models to test the effectiveness and safety of the treatment. Despite an increasing effort to find effective surrogates, animal models are still irreplaceable in gene therapy development. Rodents are important for exploring pathways and disease mechanisms and identifying potential treatment targets. However, only the primate eye resembles the human eye to a degree where most structures are nearly identical. Some research questions can therefore only be answered using a nonhuman primate (NHP) model. In this review, we want to summarize these key features and highlight the importance of the NHP model for gene therapy development in ophthalmology.
Keywords: gene therapy; drug development; animal models